2013
DOI: 10.1128/cvi.00270-13
|View full text |Cite
|
Sign up to set email alerts
|

Differential T- and B-Cell Responses to Pertussis in Acellular Vaccine-Primed versus Whole-Cell Vaccine-Primed Children 2 Years after Preschool Acellular Booster Vaccination

Abstract: cThis study investigated long-term cellular and humoral immunity against pertussis after booster vaccination of 4-year-old children who had been vaccinated at 2, 3, 4, and 11 months of age with either whole-cell pertussis (wP) or acellular pertussis (aP) vaccine. Immune responses were evaluated until 2 years after the preschool booster aP vaccination. In a cross-sectional study (registered trial no. ISRCTN65428640), blood samples were taken from wP-and aP-primed children prebooster and 1 month and 2 years post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 41 publications
4
56
0
1
Order By: Relevance
“…It is known that antibodies to the different pertussis vaccine components wane within 2 years both after wP and aP infant vaccinations (3,(7)(8)(9)(10)(11). We have found that the priming vaccination history in infancy also influences the pertussis-specific memory response, resulting in higher memory B-cell responses in aPprimed children than in wP-primed children (12).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…It is known that antibodies to the different pertussis vaccine components wane within 2 years both after wP and aP infant vaccinations (3,(7)(8)(9)(10)(11). We have found that the priming vaccination history in infancy also influences the pertussis-specific memory response, resulting in higher memory B-cell responses in aPprimed children than in wP-primed children (12).…”
mentioning
confidence: 79%
“…Already since the 1990s, acellular pertussis (aP) vaccines have been implemented in the immunization programs to replace whole-cell pertussis (wP) vaccines in many countries. In the past decade, several studies have shown that the immunity to pertussis will wane within several years after primary wP or aP vaccinations but also after the subsequent aP booster vaccinations at preschool age (1)(2)(3). In The Netherlands, three yearly peaks in the incidence of whooping cough have been observed since 1996 (4,5).…”
mentioning
confidence: 99%
“…However, we think a more likely explanation is that we failed to detect transient increases in IFN-␥ and IL-4 transcripts prior to the first sample collection or between time points. Two recent clinical studies corroborate the notion that DTaP induces Th2 and Th1 responses in children and found no significant Th17 responses following vaccination (32,33). However, there are currently no data on Th17 memory in DTwP-vaccinated and pertussis-infected children.…”
Section: Figmentioning
confidence: 95%
“…Given the resurgence in pertussis cases despite high vaccination rates, it is important to better characterize the mechanisms of immune protection against B. pertussis. While many human and mouse studies have examined the immune response to B. pertussis infection and vaccination, the exact mechanism of immunity and correlates of protection remain unclear (1,10).…”
mentioning
confidence: 99%